China's New Mania for Live Streaming: Gender Differences in Motives and Uses of Social Live Streaming Services. Issue 14 (26th August 2020) - Long, Quan; Tefertiller, Alec C.
ABSTRACT: This study examined gender differences in social live streaming service (SLSS) use by focusing on audience needs for Real-life Communication, Escape, Fun Seeking, Partnership Seeking, and Social Interaction . Results of an online survey (N = 312) of Chinese SLSS audiences' reasons for SLSS use, preferred genres, amount of usage, actual media behavior are reported. Based on Uses and Gratifications theory, we didn't find enough evidence to show that the man-dominated image of SLSS use cultivated by Chinese media is true, and we argued that the exaggerated gender differences regarding audiences' use levels and rewarding expenses were without merit. Nevertheless, we did find some differences due to gender. For example, male audiences are more likely to watch and prefer live game broadcasting, and their mediated communication is more active than females.